Partnership Strategy and Collaborative Power: Internalization of Religious Moderation in Senior High School West Nusa Tenggara Indonesia - Listiawati, Ni Putu (Jurnal Penelitian Agama Hindu, 2021)
Indonesia is a country that consists of various tribes, races, and religions. The diversity in this country does need tolerance to understand all of differences that exist. However, the degradation of the nation’s moral value is very worrying, such as intolerance within and between religious communities. Besides the frequent occurrence of fights, riots, and brawls between students and students which are very disturbing, no less important are the problem of religious moderation which also still needs to be improved. This study aims to analyze the role of partnership and collaboration strategies between school members in the internalization of various moderated values in schools. This study used qualitative analysis method. The result of this study discover that SMAN 6 Mataram has implemented several activities in the purpose of internalizing religious moderation. They internalize the value of religious moderation in every subject and conduct an activity of faith and piety every Friday. This study shows that in dealing with this problem of religious moderation, cooperation and collaboration between school members is needed because this is a shared responsibility, not just an individual. Every school member has the same responsibility in creating a peaceful and tolerant life.